The Effect of Postmethod Pedagogy Implementation in Teaching English for the Second Language Learner - Kemilau Aliffiya (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
This paper aims to review the literature on the effect of postmethod pedagogy implementation in teaching English for second language learner and to show different views from many researchers. Postmethod is the design of the classroom activity and the rules are made by the teacher based on their prior and experimental knowledge and various strategies. Postmethod pedagogy has three-dimensional system with three pedagogic element: particularity, practicality, and possibility. The postmethod pedagogy emerged to respond to the demand for a more optimal way of teaching English free from the method-based restrictions. The paper focuses on applied linguistics in English language teaching and uses a review literature method. The study found that postmethod pedagogy enables pre-service teachers to monitor their teaching process and optimize learners’ potential to learn, which affords them. Postmethod pedagogy can improved English proficiency of second language learner.